2021
DOI: 10.3390/jof7110960
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Shock Protein 60 and Pap1 Participate in the Sporothrix schenckii-Host Interaction

Abstract: Sporothrixschenckii is one of the etiological agents of sporotrichosis, a worldwide-distributed subcutaneous mycosis. Its cell wall contains a glycoconjugate composed of rhamnose, mannose, glucuronic acid, and proteins, named peptidorhamnomannan, which harbors important Sporothrix-specific immunogenic epitopes. Although the peptidorhamnomannan carbohydrate moiety has been extensively studied, thus far, little is known about the protein core. Here, using LC-MS/MS, we analyzed the S.schenckii peptidorhamnomannan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 102 publications
3
39
0
Order By: Relevance
“…In general terms, in an experimental model of systemic sporotrichosis, mice can be inoculated intraperitoneally or intravenously either in the tail vein or in the retro-orbital plexus (Tachibana et al, 1998;Fernandes et al, 1999). For a disseminated Tachibana et al, 1998;Fernandes et al, 1999;Nascimento and Almeida, 2005;Kong et al, 2006;Brito et al, 2007;Arrillaga-Moncrieff et al, 2009;Ruiz-Baca et al, 2009;Teixeira et al, 2009Teixeira et al, , 2010Almeida-Paes et al, 2012Castro et al, 2013;Clavijo-Giraldo et al, 2016;Martinez-Alvarez et al, 2019;García-Carnero et al, 2021;Song et al, 2021 Host innate response Shiraishi et al, 1992;Sassá et al, 2009;Guzman-Beltran et al, 2012;Guzman Beltrán et al, 2021;Romo-Lozano et al, 2012Sandig and Bulfone-Paus, 2012;Negrini Tde et al, 2013;de Almeida et al, 2017de Almeida et al, , 2018Martinez-Alvarez et al, 2017Lozoya-Perez et al, 2018Lozoya-Pérez et al, 2020;Lozoya-Perez et al, 2021;Rossato et al, 2019;Huang et al, 2021;Tamez-Castrellón et al, 202...…”
Section: Systemic and Peritoneal Models Of Sporotrichosis In Micementioning
confidence: 99%
See 1 more Smart Citation
“…In general terms, in an experimental model of systemic sporotrichosis, mice can be inoculated intraperitoneally or intravenously either in the tail vein or in the retro-orbital plexus (Tachibana et al, 1998;Fernandes et al, 1999). For a disseminated Tachibana et al, 1998;Fernandes et al, 1999;Nascimento and Almeida, 2005;Kong et al, 2006;Brito et al, 2007;Arrillaga-Moncrieff et al, 2009;Ruiz-Baca et al, 2009;Teixeira et al, 2009Teixeira et al, , 2010Almeida-Paes et al, 2012Castro et al, 2013;Clavijo-Giraldo et al, 2016;Martinez-Alvarez et al, 2019;García-Carnero et al, 2021;Song et al, 2021 Host innate response Shiraishi et al, 1992;Sassá et al, 2009;Guzman-Beltran et al, 2012;Guzman Beltrán et al, 2021;Romo-Lozano et al, 2012Sandig and Bulfone-Paus, 2012;Negrini Tde et al, 2013;de Almeida et al, 2017de Almeida et al, , 2018Martinez-Alvarez et al, 2017Lozoya-Perez et al, 2018Lozoya-Pérez et al, 2020;Lozoya-Perez et al, 2021;Rossato et al, 2019;Huang et al, 2021;Tamez-Castrellón et al, 202...…”
Section: Systemic and Peritoneal Models Of Sporotrichosis In Micementioning
confidence: 99%
“…Clavijo-Giraldo et al, 2016;Jellmayer et al, 2017;Lozoya-Perez et al, 2018Lozoya-Pérez et al, 2020;Lozoya-Perez et al, 2021;Manente et al, 2018;Rossato et al, 2019;García-Carnero et al, 2021;Tamez-Castrellón et al, 2021 Subcutaneous infection X XTachibana et al, 1999;Kong et al, 2006;Brito et al, 2007;Arrillaga-Moncrieff et al, 2009;Castro et al, 2013;Fernandes et al, 2013;Della Terra et al, 2017;de Almeida et al, 2018 …”
mentioning
confidence: 99%
“…Another element of the S. schenckii cell wall is the peptidorhamnomannan (PRM), a glycoconjugate composed of mannose (57%), rhamnose (33.5%), proteins (14.2%), and galactose (1%) [ 35 ]. Although the PRM has been identified as one of the main antigenic components of the cell wall and, despite its carbohydrate moiety, has been widely studied [ 35 , 36 , 37 , 38 , 39 ], the proteins that compose it were only recently identified [ 40 ]. By mass spectrometry, it was found that this complex is composed of 325 proteins, most of which lack signal peptide and, therefore, could be moonlight proteins transported to the cell surface by non-canonical secretory pathways [ 40 , 41 ].…”
Section: Cell Wall Proteinsmentioning
confidence: 99%
“…Although the PRM has been identified as one of the main antigenic components of the cell wall and, despite its carbohydrate moiety, has been widely studied [ 35 , 36 , 37 , 38 , 39 ], the proteins that compose it were only recently identified [ 40 ]. By mass spectrometry, it was found that this complex is composed of 325 proteins, most of which lack signal peptide and, therefore, could be moonlight proteins transported to the cell surface by non-canonical secretory pathways [ 40 , 41 ]. Two of these PRM proteins, Hsp60 and Pap1, were identified as adhesins that bind to different ECM proteins in the host cells [ 40 ].…”
Section: Cell Wall Proteinsmentioning
confidence: 99%
See 1 more Smart Citation